WEB-BASED ONLINE FINAL ASSIGNMENT GUIDANCE INFORMATION SYSTEM IN DIII INFORMATICS MANAGEMENT PROGRAM, EKASAKTI UNIVERSITY, PADANG - Sari, Devi Yolanda; Yahyan, Wahyuni (JENTIK, 2024)
The design of this system aims to design an effective and efficient WEB-based Online Final Assignment guidance information system for the Department of Informatics Management and can produce WEB-based Online Final Assignment guidance that can be applied in DIII Information Management at Ekasakti University, Padang. System design in this Final Project (TA) was built using a website platform that runs online. The system development method uses the System Development Life Cycle (SDLC) Waterfall which consists of 5 stages, namely, Analysis, Design, Implementation, Testing Maintenance,. The programming language used is PHP with MariaDb database. System design tools use the Unified Modeling Language (UML) method, namely UseCase Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. This final project resulted in the design of an Online Final Assignment guidance information system based on the Informatics Management Department's WEB which can assist in improving guidance services that provide convenience quickly and accurately. The design of Web-based applications in the Informatics Management DIII program is expected to help and facilitate students and supervisors in the guidance process in the Informatics Management DIII major more quickly